The Jakarta Workshop Dialogue accross the Cultural and Religious Divide in Southeast Asia - UIN Jakarta, Tim PPIM (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
The overall aim of this research project has been a) to examine the implications of recent international tensions for multi-ethnic, multi-faith societies, notably in Australia and southeast Asia; b) to evaluate the adequacy of the responses to these tensions; and c) to consider, in the light of that experience, the contribution that the dialogical approach could make to the easing of societal and international tensions. The project focused on the role of governments, media, civil society, and regional organization. For this purpose, the project selected Australia, Malaysia, Indonesia, and the Philippines as case studies, and organized two regional workshops providing a forum within which researchers, experts, and practitioners drawn primarily from these four countries were able to share their insights and analyses of the situation in their respective countriesDOI: 10.15408/sdi.v15i3.529